2020
DOI: 10.3390/vaccines8020219
|View full text |Cite
|
Sign up to set email alerts
|

The Neisseria gonorrhoeae Vaccine Candidate NHBA Elicits Antibodies That Are Bactericidal, Opsonophagocytic and That Reduce Gonococcal Adherence to Epithelial Cells

Abstract: Due to the continuing emergence of multidrug resistant strains of Neisseria gonorrhoeae there is an urgent need for the development of a gonococcal vaccine. We evaluated the gonococcal Neisseria heparin binding antigen (NHBA) as a potential vaccine candidate, in terms of its sequence conservation and expression in a range of N. gonorrhoeae strains, as well as its immunogenicity and the functional activity of antibodies raised to either the full length NHBA or a C-terminal fragment of NHBA (NHBA-c). The gene en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The non-standard of care blood sample for N. gonorrhoeae-speci c antibody assays will be allowed to clot, then centrifuged at 2,000 x g for 10 minutes at the Gold Coast Sexual Health Clinic. Serum will be aliquoted into sterile tubes and stored at −20˚C prior to transport to the Institute for Glycomics, Gri th University for analysis as per standard methods [25,[32][33][34][35]. Antibodies in blood-derived serum will be characterised using enzyme-linked immunosorbent assay (ELISA) to quantify the level of speci c antibody isotypes that cross-react with N. gonorrhoeae whole cell bacteria, and speci c target proteins) [25,[32][33][34][35].…”
Section: Sample Processing and Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-standard of care blood sample for N. gonorrhoeae-speci c antibody assays will be allowed to clot, then centrifuged at 2,000 x g for 10 minutes at the Gold Coast Sexual Health Clinic. Serum will be aliquoted into sterile tubes and stored at −20˚C prior to transport to the Institute for Glycomics, Gri th University for analysis as per standard methods [25,[32][33][34][35]. Antibodies in blood-derived serum will be characterised using enzyme-linked immunosorbent assay (ELISA) to quantify the level of speci c antibody isotypes that cross-react with N. gonorrhoeae whole cell bacteria, and speci c target proteins) [25,[32][33][34][35].…”
Section: Sample Processing and Testingmentioning
confidence: 99%
“…The ELISA titre is de ned as the reciprocal of highest serum dilution with a positive signal (i.e., a signal greater than the negative sample mean plus three standard deviations). The functional activity of antibodies against N. gonorrhoeae will be tested in serum bactericidal activity (SBA) and neutrophildependent opsonophagocytic activity (OPA) assays [32][33][34][35]. Antibody neutralisation of N. gonorrhoeae may also be tested in functional assays that measure antibody-dependent blocking of bacterial adherence to epithelial cells or of antigen binding to their ligand [33,34].…”
Section: Sample Processing and Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this antigen is conserved across Ngo genomes and has a high sequence identity among isolates. It was recently shown that recombinant NHBA is immunogenic and that anti-NHBA antibodies recognize a wide range of Ngo NHBA variants ( Semchenko et al., 2020a ). In addition, these antibodies promote C3 deposition and opsonophagocytosis.…”
Section: Nhba and Bacterial Ghostsmentioning
confidence: 99%
“…12 Meningococcal OMV proteins and NHBA are conserved and surface-exposed in N. gonorrhoeae, suggesting that MenB-4C vaccine-induced antibodies may recognize gonococcal antigenic proteins. 10,13 Murine models have shown that MenB-4C vaccine-induced antibodies cross-reacted with gonococcal antigenic surface proteins and accelerated genital gonococcal clearance. 14 In addition, MenB-4C vaccination produces antibodies in humans that recognize gonococcal antigenic proteins.…”
mentioning
confidence: 99%